The impact of TV series consumption on cultural knowledge: An empirical study based on gratification–cultivation theory - Tirasawasdichai, Tanin; Obrenovic, Bojan; Alsharif, Hussain Zaid H. (Frontiers in Psychology, 2022)
This study aims to clarify the media-induced trends of cross-cultural transmission and examine the implicit promotional potential for cultural branding. We combined the gratification and cultivation theories to explore the promotional media prospect in forming perceptions of foreign cultures’ traditions, habits, norms, and values to contribute to international communication. We analyzed the theoretical applicability in the case of China–Thailand contemporary media culture. A total of 856 Chinese series watchers were surveyed. Structural equation modeling was used to analyze the path effect of consumption of Chinese TV series on other endogenous variables. Results showed that cross-cultural media product consumption strengthens bilateral relations. Moreover, the acceptance and appropriation during engagement with media characters and producers lead to favorable attitudes toward the target culture. Results confirm the positive mutual association between the gratification and cultivation theories and their applicability in the current context. This study offers an important contribution through its finding that the need for gratification significantly and positively impacts consumption and cross-cultural learning and raises cross-cultural awareness, thereby leading to sustainable practices, and that personal engagement does not influence cultural knowledge and acceptance.